Plant Selection Behavior and Promotion Use by Garden Center Customers - Hayk Khachatryan; Alicia Rihn; Xuan Wei (EDIS)
This study explores the relationship between consumers’ plant selection behavior (i.e., shopping behavior) and ways that promotions affect subsequent activities. Written by Hayk Khachatryan, Alicia Rihn, and Xuan Wei, and published by the UF/IFAS Food and Resource Economics Department, May 2021.